Prevalence of anemia of chronic disease and iron deficiency anemia among adult diabetic patients in Erbil City - Abdulqadir, Abdulqadir Hameed; Polus, Ranan Kardagh (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Anaemia is often an unrecognized complication of diabetes mellitus that has adverse effect on the progression of diabetes related complications. Contributors to its development include erythropoietin insufficiency and iron deficiency. The aim of this study was to assess the prevalence of iron deficiency anaemia and anaemia of chronic disease among diabetic patients. Methods: Over a period of six month from November 2010 to May 2011, 250 diabetic patients, attending Layla Qasim diabetic center were studied, their age ranged between 18-73 years. Venous blood samples were collected from each of them. A complete blood picture, iron study, HbA1c% and fasting blood glucose were performed. According to the duration of diabetes, patients were divided into three groups: group I patients (duration of diabetes < 5 years), group II (duration of diabetes between 5-9 years) and group III (duration of diabetes ≥10 years). Results: One hundred ten patients (44%) were found to have anaemia. The frequency of anaemia was more among group III (46.6%). Higher prevalence of anaemia was found among female patients (53.9%) than male patient (24.1%). Among anemic patients, 72 patients (65%) considered as having anaemia of chronic disease (ACD), 26 patients (24%) were iron deficiency anemia (IDA), 11 patients (10%) were thalassemia trait and one patient (1%) had autoimmune hemolytic anaemia. ACD was more frequent among group II (80%) and group III (70.4%), while IDA was more frequent among group I (12.6%). both ACD and IDA were more frequent among female patient than male patients (34.7% and 13.8% respectively). There was no significant correlation between HbA1c and Hb, serum iron parameters and S.ferritin. Conclusion: It was concluded that anaemia is common among diabetics and remains unrecognized by both physicians and patients; it is more common among female diabetics. The commonest type of anaemia among diabetic patients is ACD followed by IDA.